2019
DOI: 10.17129/botsci.2195
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Late Pleistocene-Holocene climatic fluctuations on the phylogeographic structure and historical demographics of Zamia prasina (Cycadales: Zamiaceae)

Abstract: Background: Glacial periods during the Pleistocene have been hypothesized to have greatly influenced geographical patterns of genetic structure and demography of many tropical species. The Glacial Refugium Hypothesis proposes that, during cold, dry glacial periods, populations of moisture-affinities tropical species were restricted to sheltered, humid areas and that, during warmer and more humid interglacial periods, these populations expanded. Some mountain regions in the tropics acted as refugia during the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
3
2
0
Order By: Relevance
“…Increased environmental suitability was predicted from early to mid‐Holocene, following the gradual establishment of similar‐to‐present environmental conditions (Brenner et al., 2002; Carrillo‐Bastos et al., 2010; Metcalfe et al., 2000). Our results are concordant with phylogeographical studies of local plants (Montalvo‐Fernández et al., 2019) and mammals (León‐Tapia, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Increased environmental suitability was predicted from early to mid‐Holocene, following the gradual establishment of similar‐to‐present environmental conditions (Brenner et al., 2002; Carrillo‐Bastos et al., 2010; Metcalfe et al., 2000). Our results are concordant with phylogeographical studies of local plants (Montalvo‐Fernández et al., 2019) and mammals (León‐Tapia, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Our models for species currently endemic to the MPS-SDF match et al, 2021), in which a southbound shift for the YP populations have also been found in other taxa (Castillo-Chora, Zamudio-Beltrán, et al, 2021;Montalvo-Fernández et al, 2019). For M. mexicanus, we found widespread climatically stable areas along the MPS (see also Arbeláez-Cortés et al, 2014), while suitable conditions for the YP population and with MPS-VS, were restricted to the northern and most arid part of the YP (Paynter, 1955), which have not been documented in previous studies.…”
Section: Models Of Ypsupporting
confidence: 73%
See 2 more Smart Citations
“…This climatic change possibly caused the extinction of entire communities of boreal species, leaving only a few relict communities of endemic species or ‘paleoendemic’ species, respectively. A phylogeographic study of Zamia prasina W. Bull (Zamiaceae) shows that its populations remained restricted to the southeastern YPBP during the Last Glacial Maximum (Pleistocene-Holocene) (Montalvo-Fernández et al, 2019). Paleoclimatic reconstruction models employed in that work indicate very few or no environments available for successful establishment of populations in the YPBP at that time, which suggests scenarios of local extinction followed by the re-expansion of the distribution range throughout the warmer Mid-Holocene periods.…”
Section: Discussionmentioning
confidence: 99%